Chronic kidney disease: relation of patients with hemodialysis - Santos, Bianca Pozza dos; Oliveira, Vanessa Athaydes; Soares, Marilu Correa; Schwartz, Eda (ABCS Health Sciences, 2017)
Introduction: When kidneys lose regulatory, excretory and endocrine functions, chronic kidney disease may arrive, a slow and silent disease. When renal function is completely lost, Renal Replacement Therapies are adopted, such as hemodialysis. Objective: To know the relationship of renal chronic patients with the hemodialysis. Methods: Qualitative, exploratory and descriptive study accomplished with six patients on hemodialysis. The data collection occurred between April and May 2012 and was performed by means of semi structured interviews, being recorded in digital media and, later, transcribed in full. For the analyze data, the steps of the operative proposal of Minayo (pre-analysis, material exploration, processing of results and interpretation) were followed. The study was approved under number 36/2012 by the Research Ethics Committee. Results: Emerged the categories “installation of chronic kidney disease”, “relation with the hemodialysis machine”, “when the hemodialysis is done and the alteration of the physical appearance”, “guidance on the health care and the self-care”. Conclusion: After the discovery of the diagnosis of chronic kidney disease and the need of the hemodialysis, the patients go through a process of rejection and acceptance, which can interfere intheir emotional and psychological conditions, causing consequences in facing the disease and the treatment.